Mineral Industries Of The Middle East - Introduction - George A. Morgan (The National Institute for Occupational Safety and Health (NIOSH), 1995)
The production and processing of crude petroleum and natural gas are the dominant economic sectors of the Middle East. Development of downstream petrochemical and fertilizer industries continues as a major investment area. In 1993, the 15 countries that constituted the region accounted for 29 % of world crude petroleum output, 19 % of world natural gas plant liquid production, and 6 % of world dry natural gas production. Only Cyprus and Lebanon were not crude petroleum producers. Regional output was up for most major mineral commodities. A major exception was phosphate rock, which declined sharply owing to reduced worldwide demand. Total crude petroleum output declined by over 100 Mbbls, again owing to slack demand in the major industrial countries.